Alternate Dairy Management Practices of Feeding and Watering of Animals followed by Dairy Farmers during Drought in Patan District of Gujarat state, India - Chaudhary, D. M.; Patel, S. J.; Sheikh, A. S.; Patel, N. R.; Parmar, V. N. (Indian Journal of Hill Farming, 2017)
India is an agriculture based country and livestock sector plays an essential role in our country GDP and it is highly affected by the climatic variability such as drought, flood, etc. Drought is hazard of nature and which affects larger area and may persist for longer duration. Due to low availability of water, the forage crop production get reduced ultimately causing death of livestock due to off feed or eating of poisonous feed during scarcity period. North Gujarat region of Gujarat state comprises of six districts ofwhich Patan district was selected purposively being prone to draught. The present study was conducted in the Harij and Radhanpur talukas of Patan district. Six villages from each taluka were randomly selected. Thus, total 120 respondents were selected for the study. The data were collected by personal interview technique through a structural schedule. In Personal and socio-economic characteristics, majority of respondents (84.16 per cent) belonged to middle age group. Majority of total respondents (39.17 per cent) had low family education status. Majority of respondents (61.67 per cent) came from nuclear families. About 40.00 per cent of farmers had dairy as major occupation during drought period whereas during normal period only 25.00 per cent were in dairy business. 100 per cent of respondents amongst high income group had suffered loss in dairy during draught period. Irrespective of land holding, farmers from low income category were severely affected in terms of decrease in income up to 46.67 per cent from livestock. Herd size reduced up to 70.00 per cent during drought by the farmers owning large herds. Majority of the respondents (66.67 per cent) had experienced of more than the 10 years. In alternate dairy management practices of feeding and watering for animals include offering dry fodder to animals by 100% of respondent during drought period and mixed fodder during normal period. Concentrate mixture was being provided only to lactating animals by 68.33 per cent during drought and 87.50 per cent respondents during normal period. Majority of the farmers were neither feeding salt nor mineral mixture to the animals. Most commonly used alternate feed resource were dried fodder / hay (37.50 per cent), crop residues (33.33 per cent) and tree leaves (20.83 per cent). None of the respondent was storing the feed resources as silage for lean period as they had no knowledge about it. None of the respondent was conserving the water for drought period.